1984
DOI: 10.1002/eji.1830141018
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of a macrophage‐activating factor distinct from interferon‐γ by human T cell clones

Abstract: Supernatants from clones of human T lymphocytes that were responding to a purified Mycobacterium tuberculosis antigen were able to activate macrophages and macrophage-like myeloma cells (U937) to release increased amounts of the microbicidal agent hydrogen peroxide. The activity was not neutralized by monoclonal antibody against interferon-gamma (IFN-gamma), was greater than could be accounted for by the IFN-gamma activity in the supernatants, and was separated from IFN-gamma by high performance liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Nevertheless, the acid lability of this lymphokine in conjunction with the failure of anti-IFN-a/p to block its effect strongly suggests that IFN-y is at least partially responsible for stimulating M4~to restrict fungal growth. The recent finding that M4-activating factors distinct from IFN--y are produced by human T-cell clones also raises the possibility that IFN-y is not the only factor in culture supernatants that can stimulate M4P to exert anti-Histoplasma activity (2).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the acid lability of this lymphokine in conjunction with the failure of anti-IFN-a/p to block its effect strongly suggests that IFN-y is at least partially responsible for stimulating M4~to restrict fungal growth. The recent finding that M4-activating factors distinct from IFN--y are produced by human T-cell clones also raises the possibility that IFN-y is not the only factor in culture supernatants that can stimulate M4P to exert anti-Histoplasma activity (2).…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that a number of factors are responsible for macrophage activation, and it has been demonstrated that T-cell products contain macrophage-activating potential even after treatment with monoclonal antibodies to IFN-y (1). Thus, it may be that the various methods of activating or eliciting macrophages used in this study have different effects on the ability of the cell to respond to IFN--y. Macrophage activation is thought to involve a number of events (4, 6, 7), and it may be that thioglycolate treatment predisposes macrophages to respond to IFN, whereas the other treatments do not.…”
mentioning
confidence: 89%
“…r-IFN--y has been shown to activate macrophages in vitro (21) and also to enhance macrophage functions when administered in vivo (13). Our native lymphokine preparations certainly contain IFN--y, but there is also increasing evidence for the existence of macrophage-activating molecules distinct from IFN--y (1).…”
Section: Resultsmentioning
confidence: 96%